A novel mutation in the sulfate transporter gene SLC26A2 (DTDST) specific to the Finnish population causes de la Chapelle dysplasia. Issue 12 (15th August 2008) - Bonafé, L; Hästbacka, J; de la Chapelle, A; Campos-Xavier, A B; Chiesa, C; Forlino, A; Superti-Furga, A; Rossi, A
Abstract : Background: Mutations in the sulfate transporter gene SLC26A2 ( DTDST ) cause a continuum of skeletal dysplasia phenotypes that includes achondrogenesis type 1B (ACG1B), atelosteogenesis type 2 (AO2), diastrophic dysplasia (DTD), and recessive multiple epiphyseal dysplasia (rMED). In 1972, de la Chapelle et al reported two siblings with a lethal skeletal dysplasia, which was denoted "neonatal osseous dysplasia" and "de la Chapelle dysplasia" (DLCD). It was suggested that DLCD might be part of the SLC26A2 spectrum of phenotypes, both because of the Finnish origin of the original family and of radiographic similarities to ACG1B and AO2. Objective: To test the hypothesis whether SLC26A2 mutations are responsible for DLCD. Methods: We studied the DNA from the original DLCD family and from seven Finnish DTD patients in whom we had identified only one copy of IVS1+2T>C, the common Finnish mutation. A novel SLC26A2 mutation was found in all subjects, inserted by site-directed mutagenesis in a vector harbouring the SLC26A2 cDNA, and expressed in sulfate transport deficient Chinese hamster ovary (CHO) cells to measure sulfate uptake activity. Results: We identified a hitherto undescribed SLC26A2 mutation, T512K, homozygous in the affected subjects and heterozygous in both parents and in the unaffected sister. T512K was then identified as second pathogenic allele in the seven Finnish DTD subjects. Expression studies confirmed pathogenicity. Conclusions: DLCD is indeed allelic to the other SLC26A2 disorders. T512K is a second rare "Finnish" mutation that results in DLCD at homozygosity and in DTD when compounded with the milder, common Finnish mutation.